Performance evaluation of young alpine skiers in laboratory and during skiing - Besseghini, A.; Pozzo, R.; Cas, F. D.; Canclini, A.; Canclini, A. (9th International Congress on Science and Skiing, March 18 - 22, 2023, Saalbach-Hinterglemm, Austria, 2023)
INTRODUCTION: Alpine skiing is influenced by a combination of physiological/functional parameters and psychological decision-making. Factors such as muscular strength, agility, balance, coordination, flexibility, anaerobic and aerobic capacities play a crucial role in alpine ski-racers performance 1. The purpose of this study is to evaluate the most important capacities at the beginning and at the end of the off-season periodization. Skiing performance on a slope was also checked.